P124: Determining ED staff awareness and knowledge of intimate partner violence and available tools. (15th May 2017) - Vonkeman, J.; Atkinson, P.R.; Fraser, J.; McCloskey, R.
Abstract : Introduction: Domestic violence (DV) rates in smaller cities have been reported to be some of the highest in Canada. It is highly likely that emergency department staff will come across victims of intimate partner violence (IPV) in their daily practice. Elsewhere we have found low rates of IPV documentation as well as underutilization of current tools in the ED. The purpose of this study is to describe ED staff awareness and knowledge surrounding IPV, currently accepted screening questions, and available screening tools.Methods: To assess awareness and knowledge, a cross-sectional online survey was distributed to ED staff (LPNs, NPs, Physicians, Residents, RNs) via staff email lists three times between July and October 2016, with a response rate of 45.9% (n=55). The primary outcomes were correct identification of appropriate IPV questions. Secondary outcomes included awareness of screening tools (HITS, WAST, PVS, AAS), whose role it is to question patients, and whether or not formal training has been received.Results: When asked to identify recommended questions for asking about IPV, staff were more likely to choose screening questions (75.3%; 95% CI 69.3% to 80.6%) compared to questions that are not recommended (23.8%; 95% CI 19.4% to 30.7%). However, 87.3% of respondents were not aware of current screening tools. 49.1% believed that all patients with typical injuries (ex. facial injury), should have further questioning about IPV, 20% believed that all patients with any injury, and 16.4% believed that all patients should be questioned about IPV. 89.1% also felt that it is both the physician and nurse's role to question patients about IPV. Finally, 81.8% of ED staff did not receive any formal training on domestic or intimate partner violence.Conclusion: The present study indicates that there may be a gap in education surrounding this high risk condition as seen by the lack of knowledge surrounding current tools, lack of consensus on who should be questioned, and lack of training. Therefore, introduction of a knowledge translation piece may be beneficial to both ED physicians and nurses.